Coaching Dan Kinerja Perawat (Studi Kasus Pada Rumah Sakit Umum Daerah Cibinong, Kabupaten Bogor, Jawa Barat) - Budi Hartono; Johanes Jakri; Komala Sari (Poltekkes Kemenkes Surakarta, 2019)
Background: Nurses can use coaching as the way to empower quality of their skillsto have excellent services in hospital. Coaching is a tool that can improve motivation and performance of nurses. The research is aimed to get explanation about the relation of coaching, motivation and performance at a regional hospital. Method: Methodology research is correlationalcrosssectionalstudy with 30 nurses as respondents. Path analysis are used as statistical tools. Result: The result of this study shows that R² is about 0.704; it means that coaching has a direct, positive and significant impact to motivation and performance of nurses. Motivation has a direct, positive and significant impact to the performance of the nurses (R-value = 0.848). Coaching has an indirect, positive and significant impact to the performance of nurse through job motivation (R-value = 0.737). Conclusion: Conclusions of this study is coaching can increase nurse potential related to work motivation, coaching aims at increasing the potential of nurses who are performance oriented. Planning, implementation and evaluation of empowerment programs with effective coaching methods can ultimately improve the quality and accountability of nurses performance. Result of this research implied that the use of coaching could improve motivation and performance for nurse in hospital.